The Influence Of Product Quality, Brand Image And Electronic Word Of Mouth On The Purchasing Decision Of Ms Glow For Men Facial Wash In Jagakarsa, South Jakarta - Kumba Digdowiseiso; Muhammad Naufal Tarmizi; Resti Hardini (Syntax Corporation Indonesia, 2023)
This study aims to determine Product Quality, Brand Image and Electronic Word of Mouth on the Purchase Decision of Ms Glow for Men Facial Wash. The data analysis technique used multiple linear regression and used SPSS version 23. The results of the researchers found the regression equation Y = 0.347 X1 + 0.297 X2 + 0.340 X3. t count 4.113 > 1.660 t table and sig value 0.00 < 0.50. For Brand Image (X2) has a positive and significant effect on Purchase Decision (Y) based on t count 3.567 < 1.660 t table and sig value 0.01 > 0.50. For Electronic Word of Mouth (X3) has a positive and significant effect on Purchase Decision (Y) based on t count 4.879 > 1.660 t table and sig value 0.00 < 0.50. Among the third, most significant variables is the Product Quality variable (X1) based on t count 4.113 > 1.660 t table and sig value 0.00 < 0.50. The results of this study are expected to be a reference material to improve Product Quality (X1) and (X2) Brand Image that can support Purchase Decisions (Y)